Analysis of State Responsibility for Health Rights in Indonesia: Integrating Legal Positivism and Justice Theory - Raymond R. Tjandrawinata; Ina Heliany (Eduvest - Journal of Universal Studies, 2025)
This research examines the legal and moral dimensions of the state's responsibility for the right to health in Indonesia by synthesizing legal positivism and contemporary theories of justice. Focusing on Law No. 17 of 2023 on Health and the National Health Insurance scheme (Jaminan Kesehatan Nasional, JKN), the research argues that formal legal validity alone is insufficient to discharge the state’s constitutional obligations. While Indonesia has constructed a procedurally coherent health law framework that satisfies positivist criteria of legality, significant gaps remain in the realization of substantive justice, particularly for disadvantaged populations. By juxtaposing H.L.A. Hart’s conception of legal validity with John Rawls’s theory of justice as fairness, this study demonstrates that the legitimacy of health law must be assessed not only by its formal pedigree but also by its distributive consequences. The research concludes that state responsibility for health rights requires an integrated approach in which legal positivism is complemented—and normatively corrected—by justice-based evaluation, thereby proposing a dual-threshold conception of state responsibility in health law that distinguishes legal validity from normative legitimacy through doctrinal analysis and normative institutional evaluation. This study conceptually reframes state responsibility for social rights as a dual-threshold structure in which formal legality constitutes a necessary condition of obligation, while distributive justice operates as an independent condition of legitimacy.